Students’ Perceptions of Using English Learning Applications to Enhance Vocabulary Mastery - Nuranantya Mersa Ukkas; Aminah Suriaman; Moh. Abraham Akbar Eisenring; Afrillia Anggreni (Journal of English Language and Education, 2026)
Mobile-Assisted Language Learning (MALL) has provided university students with flexible opportunities to improve vocabulary mastery through English learning applications. This study investigated English Education students’ perceptions of using such applications for vocabulary learning at Tadulako University. A qualitative descriptive design was employed involving 69 students who completed a Likert-scale questionnaire and five participants who took part in semi-structured interviews. Data were analyzed using descriptive statistics and thematic analysis. The findings revealed that students generally perceived English learning applications positively because they helped them learn new words, improve pronunciation, increase confidence, and support autonomous learning. Features such as gamification, repetition, quizzes, and audio pronunciation enhanced motivation and engagement. However, students also reported several limitations, including insufficient contextual explanations, repetitive activities, unstable internet connections, and premium-feature restrictions. Overall, English learning applications were perceived as effective supplementary tools for vocabulary development rather than complete replacements for classroom instruction and authentic communication practice. The study highlights the potential of MALL applications to support independent vocabulary learning while emphasizing the continued importance of teacher guidance and interactive language use.